Theoretical Analysis In Fuzzy Temporal Knowledge - Abdul Manaf, Nor Azlinayati (2007)
In this study, a framework that can handle the uncertainty of temporal information is proposed. this framework can deal with both imprecise temporal intervals and imprecise temporal relations.